The Role of Innovation on Performance in Banking Sector: A Bibliometric Analysis - Tina Sekar Ayuning Tyas; Syarifa Hanoum; Santy Dwi Cempaka; Uliyatun Nikmah (International Journal of Business and Management Technology in Society, 2025)
Purpose – The banking industry has undergone significant transformation in recent decades, driven by rapid technological advances and regulatory changes. This study aims to explore the development of research related to the impact of innovation on banking performance. Methodology – This study analyses a total of 211 full-text articles from Scopus database using VOSViewer software and content analysis approach. Findings – This study found a significant increase in publications related to banking innovation since 2013. The journals "Sustainability Switzerland" and "Technological Forecasting and Social Change" are the main sources of publications and citations. The United States and China lead in the number of publications. Bibliographic coupling analysis identified 10 clusters with their respective main themes, including factors influencing firm performance, banking strategy, fintech adoption, SME growth, and the influence of organizational culture and intellectual capital. Further content analysis revealed that quantitative research dominates existing literature; product innovation is the most frequently discussed type of innovation; and financial and non-financial performance are often discussed together in a single article. Originality – This study provides a systematic bibliometric synthesis that integrates publication trends, thematic clusters, and content characteristics, thereby offering a comprehensive overview of how innovation–performance relationships have been examined in the banking sector. Research limitations – Articles analyzed limited to article and review publications in English until June 2024 available in Scopus. Practical implications – Banks need to pursue customer-centric and secure innovation through strategic investment in digital technologies, effective risk management, collaboration with fintech firms, and continuous human capital development within a robust regulatory framework.